Qualidade microbiológica e físico-química do requeijão do Norte de Minas Gerais - Luana Michelle de Melo (2016)
The adoption of quality indicators in raw milk is one of the main measures to improve the quality of dairy products. The objectives of this study were to evaluate the relationship of quality indicators, somatic cell count (SCC) and total bacterial count (TBC) with the chemical composition of the milk, and the physical-chemical and microbiological quality of the dark cheese. The results were expressed by descriptive statistics. For the correlations of SCC data and TBC milk between the physical and chemical composition of the curd were estimated Pearson's correlation coefficient. The average chemical composition of milk is shown within the normal range for cattle, however, it was found to increase the fat content. This condition may mask the actual quality of milk, due to the appreciation of its solid components, especially in the production of dairy products. The SCC average observed in milk was 3.01 x 105 cells / mL presenting lower than recommended by law, however, this result suggests the presence of subclinical mastitis in the herd. The average milk TBC performed-high 2.94 x 104 UFC / mL. As for the physicochemical characterization of cheese, there was variation of the parameters analyzed, showing a lack of standardization in the manufacturing process. The sanitary conditions of the final product were found to be unsatisfactory due to the counting of microorganisms indicators of poor hygiene. For Escherichia coli, there was an average of 1.46 x 103 UFC / mL. In total coliform count was found to average 2.0 x 106 UFC / mL. Staphylococcus spp high counts were observed. 2.10 x 106 UFC / mL. As for the correlation between SCC and its influence on milk constituents, there was moderate correlations between SCC and protein 0.364421 and SCC and ash - 0.48535. Regarding the correlation between CBT and the variables studied, only the protein content was negatively correlated with the CBT - 0.684720. The data suggest the need for standardization in the manufacturing process of the curd and implementation of quality improvement programs and food safety.